Qu’est-ce que le Street art ? Essai et discussion des définitions - Ulrich Blanché (Cahiers de Narratologie)
Cedar Lewisohn, curator of the Street Art show at Tate Modern (2008), blustered in an international street art conference in Lisbon (2014) about Street Art academics being rather fans than critical academics. Most Street Art researchers may not write without critical distance, but most papers given at Street Art conferences are rather descriptive. We often just describe Street Art projects, often without explaining how we use the term Street Art.When Lewisson says, Street Art research is just written by fans he might be right for what he reads. I impute to Lewisohn that he hardly ever read any Street Art academic writing that is not English but French, Swedish, German or Italian. So this whole « fan thing » might be just a problem of communication.« What is Street Art ? ». This was the first question in a call for Paper for a Street Art conference in New York in March as well as in the Nice conference. Since about 2005, a range of academic authors already tried to answer that question. A lot of them do not write in English. My paper is a short introduction and discussion of the term Street Art and related terms from the position of a visual culture researcher. First and foremost I discuss the following attempt of a definition:Street Art consists of self-authorized pictures, characters, and forms created in or applied to surfaces in the urban space that intentionally seek communication with a larger circle of people. Street Art is done in a performative and often site-specific, ephemeral, and participatory way. Street Art is mostly viewed online. It differs from Graffiti and Public Art.